Belgium : 2017 Article IV Consultation-Press Release; Staff Report; Supplementary Information. (IMF Staff Country Reports; Country Report, 2017)
This 2017 Article IV Consultation highlights Belgium's recovery, which is expected to strengthen modestly in 2017, with real GDP projected at 1.6 percent. The medium-term outlook remains constrained by structurally weak growth in advanced economies. Downside risks are significant, including those related to global and regional uncertainties that could affect trade and financial markets. Fiscal sustainability therefore remains tenuous and sensitive to potential shocks. Although private employment has been recovering, there is entrenched high unemployment and inactivity among certain groups, including the young, those with few skills, and immigrants from outside the European Union.